Disclosure of Islamic Values and Their Impact on Third-Party Funds and Islamic Bank Financing - Muchlis, Mustakim (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study investigates how the disclosure of Islamic values may contribute to third-party funds and financing in Islamic-compliant banks. This study employs a sample of 12 Islamic commercial banks in Indonesia with panel data from 2015 to 2020. Weights, based on expert assessments to determine the level of Islamic values, present as the academic contribution of this research. The finding reports that exposure to Islamic values negatively and significantly impacts financing. Third-party funds provide an indirect positive relationship between the disclosure of Islamic values and financing. These findings further consider the importance of implementing and disclosing Islamic values for investors.